Exosomes: a significant medium for regulating drug resistance through cargo delivery - Ren, Bixuan; Li, Xiaoqing; Zhang, Zhihua; Tai, Sheng; Yu, Shan (Frontiers in Molecular Biosciences, 2024)
Exosomes are small lipid nanovesicles, having a diameter of 30 to 150 nm. They are present in all body fluids and are actively secreted by the majority of cells through the process of exocytosis. Exosomes play an essential part in intercellular communication and act as significant molecular carriers in regulating various physiological and pathological processes, such as the emergence of drug resistance in tumor. Tumor-associated exosomes transfer drug resistance to other tumor cells by releasing substances such as multidrug resistance proteins and miRNAs through exosomes. These substances change the cell phenotype, making it resistant to drugs. Tumor-associated exosomes also have function in impacting drug resistance in other cells like immune cells, stromal cells. Exosomes alter the behavior and function of these cells to help tumor cells evade immune surveillance and form a tumor niche. In addition, exosomes also export substances such as tumoricidal drugs and neutralizing antibody drugs to help tumor cells resist drug therapy. In this review, we sum up the mechanisms of exosomes in promoting drug resistance by delivering cargo in the context of tumor microenvironment(TME).